Conformational Selection of Dimethylarginine Recognition by the Survival Motor Neuron Tudor Domain. Issue 2 (8th December 2017) - Supekar, Shreyas; Papageorgiou, Anna C.; Gemmecker, Gerd; Peltzer, Raphael; Johansson, Mikael P.; Tripsianes, Konstantinos; Sattler, Michael; Kaila, Ville R. I.
Abstract: Tudor domains bind to dimethylarginine (DMA) residues, which are post‐translational modifications that play a central role in gene regulation in eukaryotic cells. NMR spectroscopy and quantum calculations are combined to demonstrate that DMA recognition by Tudor domains involves conformational selection. The binding mechanism is confirmed by a mutation in the aromatic cage that perturbs the native recognition mode of the ligand. General mechanistic principles are delineated from the combined results, indicating that Tudor domains utilize cation–π interactions to achieve ligand recognition. Abstract : The House of Tudor : The Tudor domain of the human survival motor neuron protein selectively recognizes stereoisomers of dimethylarginine residues within its aromatic ligand‐binding cage using cation–π interactions. Stereoselectivity can be modulated by a single point mutation.